Achmatowicz reaction: A versatile tool in bioactive natural products synthesis - Mahajan, Pankaj S.; Humne, Vivek T.; Mhaske, Santosh B. (Current Organic Chemistry, 2017)
Achmatowicz reaction has emerged as an efficient tool in organic synthesis since its discovery in 1971 by Achmatowicz Jr. The original protocol went through several advantageous variations. Biocatalytic and metal catalyzed versions of this reaction are some of the significant achievements, which further enhanced its effectiveness. The pyranone product of the Achmatowicz reaction is a versatile building block for the synthesis of bioactive scaffolds, drugs and natural products. The present review covers the application of the Achmatowicz reaction in the synthesis of natural products and bioactive molecules reported from 1971 to date. It has been divided into seven sections on the basis of the core structures of the natural products synthesized utilizing the Achmatowicz reaction. We believe that this comprehensive review will attract many more organic chemists to explore its utility in organic synthesis, especially in the synthesis of bioactive natural products as well as drugs in their efficient and atom economical synthesis.
Keywords: Achmatowicz reaction; carbohydrates; Furanols; Natural products; pyranones; Total synthesis